Jega's Words Of Wisdom - Former Olympian wishes BJSS graduates a bright future - The Star, Ng Wei Loon (2008)
Former olympian Datuk Dr M. Jegathesan inspired the current batch of Bukit Jalil Sports School (BJSS) pre-university graduates to embark on their brilliant careers with his rousing words of wisdom.